Effect of Vitamin D Receptor Activators on Glomerular Filtration Rate: A Meta-Analysis and Systematic Review. - Qian Zhang; Ming Li; Tiansong Zhang; Jing Chen (PLoS ONE, 2016)
Background Vitamin D receptor activators (VDRAs) can protect against mineral bone disease, but they are reported to elevate serum creatinine (SCr) and may also reduce glomerular filtration rate (GFR). Methods We conducted a systematic review and meta-analysis of randomized clinical trials (RCTs) to evaluate the effect of VDRAs on kidney function and adverse events. MEDLINE, EMBASE, the Cochrane Controlled Trials Register were searched for RCTs that evaluate vitamin D receptor activators (alfacalcidol, calcitriol, doxercalciferol, falecalcitriol, maxacalcitol and paricalcitol) up to March 2015. Results We included 31 studies, all of which were performed between 1976 and 2015, which enrolled 2621 patients. Patients receiving VDRAs had lower eGFR (weighted mean difference WMD -1.29 mL/min /1.73 m2, 95% CI -2.42 to -0.17) and elevated serum creatinine (WMD 7.03 μmol/L, 95% CI 0.61 to 13.46) in sensitivity analysis excluding studies with dropout rate more than 30%. Subgroup analysis of the 5 studies that not use SCr-based measures did not indicated lower GFR in the VDRAs group(WMD -0.97 mL/min/1.73 m2, 95% CI -4.85 to 2.92). Compared with control groups, there was no difference in all-cause mortality (relative risk RR 1.41, 95% CI 0.58 to 3.80), cardiovascular disease (RR 0.84, 95% CI 0.42 to 1.71), and severe adverse events (RR 1.15, 95% CI 0.75 to 1.77) for the VDRAs groups. Episodes of hypercalcemia (RR 3.29, 95% CI 2.02 to 5.38) were more common in the VDRAs group than in the control group. Conclusions Administration of VDRAs increased serum creatinine levels. Subgroup analysis of studies that did not use SCr-based measures did not indicate a lower GFR in the VDRA group. Future studies with non-SCr-based measures are needed to assess whether the mild elevations of serum creatinine are of clinical significance.